2010
DOI: 10.1111/j.1440-1789.2009.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological study of pseudohypertrophy of the inferior olivary nucleus

Abstract: There have been only a few reports about the immunohistochemical study of pseudohypertrophy of the inferior olivary nucleus (PH-IO). We therefore performed the detailed immunohistochemical study of 10 PH-IOs in 8 patients to clarify the mechanism of neuronal degeneration and its related phenomenon of PH-IO. We used various antibodies to alphaB-crystallin (alphaBC), synaptophysin (SYP), microtubule-associated protein 2 (MAP2), Lys-Asp-Glu-Leu (KDEL) receptors, heat shock protein (HSP) 27 as well as SMI-31. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These pathological hallmarks have been thought to result from transynaptic degeneration secondary to a lesion of the ipsilateral central tegmental tract or the contralateral dentate nucleus. More recent immunohistochemical studies identified various changes in the neurons, their neurites, and presynaptic terminals confirming this hypothesis (74, 75). The main finding is a decreased synaptophysin immunoreactivity confirming the presynaptic abnormalities linked to deafferentation (75).…”
Section: Neuropathology Of the Degenerative Hypertrophic Inferior Olimentioning
confidence: 61%
See 1 more Smart Citation
“…These pathological hallmarks have been thought to result from transynaptic degeneration secondary to a lesion of the ipsilateral central tegmental tract or the contralateral dentate nucleus. More recent immunohistochemical studies identified various changes in the neurons, their neurites, and presynaptic terminals confirming this hypothesis (74, 75). The main finding is a decreased synaptophysin immunoreactivity confirming the presynaptic abnormalities linked to deafferentation (75).…”
Section: Neuropathology Of the Degenerative Hypertrophic Inferior Olimentioning
confidence: 61%
“…More recent immunohistochemical studies identified various changes in the neurons, their neurites, and presynaptic terminals confirming this hypothesis (74, 75). The main finding is a decreased synaptophysin immunoreactivity confirming the presynaptic abnormalities linked to deafferentation (75). In 1981, Goto and Kaneko published a neuropathological study of eight cases of pontine hemorrhage involving unilaterally or bilaterally central tegmental tracts with different survival periods (76).…”
Section: Neuropathology Of the Degenerative Hypertrophic Inferior Olimentioning
confidence: 61%
“…12 Previous studies have reported neuropathological findings, including neuronal positivity for αB-crystallin (αBC), p-NFP (SMI31), microtubuleassociated protein 2 (MAP2), Lys-Asp-Glu-Leu (KDEL) receptors, and presence of synaptophysin-positive granules to be associated with inferior olivary hypertrophy. 13,14 However, the expression levels of these proteins among patients, including that of αBC, showed large variance, 14 suggesting the possible involvement of several cellular pathways in inferior olivary hypertrophy. The inferior olivary hypertrophy observed in our case was "isolated", possibly induced by a special mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Second, central tegmental tract connects the red nucleus to ipsilateral ION at the medulla. Last, ION sends efferents through the inferior cerebellar peduncle, terminating at the contralateral dentate nucleus, which ends up forming the dentate-rubral-olivary circuitry [9][10][11][12][13][14]. A lesion in any part of this synaptic pathway may result in HOD and is accompanied, due to deafferentation, by atrophy of ipsilateral midbrain and contralateral cerebellar hemisphere, exactly as our patient.…”
Section: Discussionmentioning
confidence: 99%